Increased lymphocyte viability after non-stimulated peripheral blood mononuclear cell (PBMC) culture in patients with X-linked lymphoproliferative disease (XLP) - Belmonte de Zalar, Liliana Elizabeth (2009)
Survival of lymphocytes after prolonged culture was studied in two asymptomatic XLP patients. Viability of XLP PBMC after 30 days of non-stimulated culture was higher than that of normal controls (N), mainly due to the persistence of CD8 memory lymphocytes. IFNγ high CD8 T lymphocytes remained higher in XLP than in N after 30 days. The number of perforin+ CD8 lymphocytes was markedly reduced after 30 days in XLP and in N. Increased viability was not related to CD127, PD-1, CD27, or CD62L expression. Concerning B lymphocytes, memory CD27+ CD19+ cells prevailed over CD27- cells after 30 days in both XLP and N, with far more surviving cells in XLP. In N, few CD19+ B lymphocytes were viable after prolonged culture. In XLP, these cells were also IgD+, IgM+ and EBNA2+. These results demonstrate that IFNγ-positive memory CD8 T cells persist in XLP after prolonged culture in association with a subset of viable memory CD27+ B cells expressing latent EBV antigens. The survival advantage of XLP cells might be related to increased frequency of extranodal lymphoma in XLP patients. © 2009 Elsevier Inc. All rights reserved.